SEARCH ENGINE OPTIMIZATION PADA INSTITUTIONAL REPOSITORY BERBASIS OPEN JOURNAL SYSTEM - Nugraha, Fitra (BUFFER INFORMATIKA, 2018)
ABSTRACT The process of publishing journal articles and research student at the Kuningan University is not optimal, the results of research files are only stored in computer study program, and the print version published in the University library and each department. The title and theme of the research that has been done by all students who have graduated not organized, so it is relatively hard to find a title of the research has been done or not. Search Engine Optimization is the process of optimizing an application for easy access by the search engine. Institutional Repository is the digital storage media for the research sector in an institution that can be accessed anytime and more resistant to damage. Open Journal System is one of the international application as a digital repository of scientific articles and publications online and it might apply in the environment Kuningan University for infrastructure and infrastructure already supports. This research aims to implement the application Open Journal Systems at the Kuningan University and process optimization of search Google Search and Google Scholars and Portal Garuda so can the search engines will easily access content that is applied Institutional Repository, which will raise the rating is displayed search results in google engines and improve rankings webometrics Keywords: Search Enggine Optimization, SEO, Digital Repository, OJS, Google Search, Google Schoolar